The complete chloroplast genome of Scurrula chingii (W.C. Cheng) H.S. Kiu (Loranthaceae), a hemiparasitic shrub. Issue 1 (2nd January 2021) - Li, Manru; Zhang, Yifei; Li, Yuanjie; Zhang, Ling
Abstract: Scurrula chingii (W.C. Cheng) H.S. Kiu is a stem hemiparasite of the genus Scurrula in the family Loranthaceae distributed in southwest China and northern Vietnam. Here, we report and characterize the complete plastid genome sequence of S. chingii to provide genomic resources useful for the phylogenetic studies of Santalales. The plastome of S. chingii is 122, 764 bp in length, consisted of a large single-copy region (70, 726 bp), a small single-copy region (6, 091 bp), and a pair of inverted repeat regions (22, 974 bp). The GC content of the whole plastome is 37.2%. It contains 109 genes, including 69 CDS (protein-coding genes), eight rRNAs, and 32 tRNAs. The alignment of 14 species complete chloroplast genomes of Loranthaceae was implemented and a phylogenetic tree was constructed using maximum-likelihood (ML) method, which revealed that S . chingii clustered with Scurrula parasitica and Taxillus thibetensis as a monophyletic group.